1995
DOI: 10.1074/jbc.270.18.10551
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Conformational Changes Induced by 20-epi Analogues of 1α,25-Dihydroxyvitamin D3 Are Associated with Enhanced Activation of the Vitamin D Receptor

Abstract: The relative affinities of the 1 alpha,25-dihydroxyvitamin D3 (1,25-D3) analogues 20-epi-1 alpha,25-dihydroxyvitamin D3 (IE) and 20-epi-22-oxa-24a,26a,27a-tri-homo-1 alpha,25-dihydroxyvitamin D3 (ID) to the nuclear vitamin D receptor (VDR) are similar to that of 1,25-D3, but their antiproliferative action is 1000-fold greater. We tested whether the greater antiproliferative effect of these analogues is due to a differential activation of the VDR. In ROS 17/2.8 cells, the effective doses required to produce 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 25 publications
7
145
1
Order By: Relevance
“…7, A and B). To our knowledge the flexible docking protocol used to generate this hypothesis is the first simulation that lacks bias in the conformation and placement of the ligand within the VDR LBP (7,30,32). Importantly, the average 1,25D/MK⅐hVDRwt ⌬G binding values (Table 3) qualitatively support the fact that a 10-fold excess of MK is required to be an efficient 1,25D-hVDR antagonist (Figs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…7, A and B). To our knowledge the flexible docking protocol used to generate this hypothesis is the first simulation that lacks bias in the conformation and placement of the ligand within the VDR LBP (7,30,32). Importantly, the average 1,25D/MK⅐hVDRwt ⌬G binding values (Table 3) qualitatively support the fact that a 10-fold excess of MK is required to be an efficient 1,25D-hVDR antagonist (Figs.…”
Section: Discussionmentioning
confidence: 51%
“…The ϳ34-kDa hVDRwt fragment stabilized by 1,25D represents the active, closed conformation of helix-12 (hVDR-c1, Fig. 5A) (20,30). The MK-H305F and MK-H305F/H397F PSA results demonstrated that MK did stabilize a strong hVDR-c1 band (Fig.…”
Section: Mk Stabilizes the Active Closed Hvdr Helix-12 Conformation mentioning
confidence: 87%
“…The reaction tubes were incubated for 2 h at 30°C, then placed on ice. The 1,25D or analog (10 Ϫ5 M) was added, the tubes were incubated at room temperature for 20 min (28), and then 15 g͞ml trypsin was added to the tubes and incubated for 20 min at room temperature, followed by a 5-min incubation at 80°C with SDS. After SDS͞PAGE, bands were visualized by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Currently the most actively used method for assaying VDR H12 conformational heterogeneity in solution, is the partial trypsin digest experiment (protease sensitivity assay, PSA) [17]. Unlike x-ray crystallography, PSA provides insight into solution state H12 dynamics and ultimately yields insight into the population distribution of apo/holo-VDR (H12) isomers under steady state conditions.…”
Section: Introductionmentioning
confidence: 99%